Firm's knowledge creation structure for new product development - Hong Y. Park; Hyejung Chang; Yong-Seung Park; Tahir Nisar (Cogent Business & Management, 2015)
Knowledge has many different characteristics and scholars in epistemology, economics and management have dealt with them ever since knowledge has emerged as the leading source of firms' competitive advantages. New product development requires new ideas and new ideas are stemming from knowledge. Knowledge originates from tacit knowledge. Therefore, firms need to enact tacit knowledge. Enactment takes different forms depending on the context of knowledge and organizational characteristics. This paper conducts an in-depth literature review on the nature of knowledge and knowledge creation structure and investigates how The Dow Chemical Company uses a knowledge creation structure to elicit tacit knowledge and exploit knowledge for new product development. The Dow Chemical Company is known as one of the leading innovative firms in the world. We believe that this case enriches research on knowledge creation and new product development although it has limitations in generalizing its findings and practices. In solidifying the knowledge-based theory of the firm, we need a multi-dimensional approach such as a survey, case study, and theory development. This study develops a knowledge creation theory and apply it to the real business case.
Keywords: 650